2022
DOI: 10.3389/fphar.2022.899038
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Strategy to Identify and Quantify the Quality Markers of Xinkeshu Tablets Based on Spectrum-Effect Relationship, Network Pharmacology, Plasma Pharmacochemistry, and Pharmacodynamics of Zebrafish

Abstract: Xinkeshu tablets (XKST), a traditional Chinese patent medicine (CPM), have served in the clinical treatment of cardiovascular diseases (CVDs) for decades. However, its pharmacodyamic material basis was still unclear, and the holistic quality control has not been well established due to the lack of systematic research on the quality markers. In this experiment, the heart rate recovery rate of a zebrafish larva was used to evaluate the traditional pharmacological effect of XKST i.e., antiarrhythmic effect. The H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…It was found that tanshinones and flavonoids were potential anti-neuroinflammatory compounds in the preparation. Furthermore, many achievements have been made in the quality evaluation of Xinkeshu Tablets [78], Rong'e Yishen oral liquid [79] and other TCM preparations by spectrum-effect relationships.…”
Section: Quality Evaluation Of Tcmmentioning
confidence: 99%
“…It was found that tanshinones and flavonoids were potential anti-neuroinflammatory compounds in the preparation. Furthermore, many achievements have been made in the quality evaluation of Xinkeshu Tablets [78], Rong'e Yishen oral liquid [79] and other TCM preparations by spectrum-effect relationships.…”
Section: Quality Evaluation Of Tcmmentioning
confidence: 99%